2004
DOI: 10.4015/s1016237204000281
|View full text |Cite
|
Sign up to set email alerts
|

Using Electrical Conductance as the Evaluation Parameter of Pain in Patients With Low Back Pain Treated by Acupuncture Like Tens

Abstract: This study was to objectively evaluate the treatment effect of acupuncture-like transcutaneous electrical nerve stimulation (AL-TENS) on patients with low back pain. Fifty patients suffering from low back pain for at least three months were involved in the study from Chang Gung Memorial Hospital. The subjects were treated with TENS (100 Hz) on acupuncture points (BL23 and BL25). Two electrodes were placed on two right acupoints and two electrodes on the left. Pulse duration of electrical stimulation was fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The results also demonstrated that the reason for the increase of electrical conductance could be the soothing of nerve and muscle and improving of local blood circulation in the deep tissue which were stimulated by the frequency of 5 KHz [22][23][24][25]; whilst the decrease of VAS was the analgesic effect caused by the frequency of either 2 Hz or 100 Hz [17,36].…”
Section: Table II Electrical Conductances (Mean Sem) Of Meridians Anmentioning
confidence: 89%
See 2 more Smart Citations
“…The results also demonstrated that the reason for the increase of electrical conductance could be the soothing of nerve and muscle and improving of local blood circulation in the deep tissue which were stimulated by the frequency of 5 KHz [22][23][24][25]; whilst the decrease of VAS was the analgesic effect caused by the frequency of either 2 Hz or 100 Hz [17,36].…”
Section: Table II Electrical Conductances (Mean Sem) Of Meridians Anmentioning
confidence: 89%
“…In our previous research [34][35][36], healthy control and sham control as well as 2 Hz and 100Hz frequency modes of TENS without modulated frequency of 5 KHz were studied. The data from previous studies showed that there was no significant difference in electrical conductances of meridians or acupoints before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also various studies in recent years to diagnose the LBP based on skin conductivity as a replacement method for the VAS [7][8][9]. Although there have been a great deal of research coping with the LBP in the literature, in terms of the VAS scale and the resistance, the prediction of the LBP using the ANN and ANFIS has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…But these devices are inadequate in practical application. From a technical standpoint, the main inadequacies are as follows:811…”
Section: Introductionmentioning
confidence: 99%